Social Networks and the Labour Market - Farzana Afridi; Amrita Dhillon (Institute of Labor Economics (IZA), 2022)
This chapter surveys recent literature on social networks and labour markets, with a specific focus on developing countries. It reviews existing research, in particular, on the use of social networks for hiring and the consequences of networks for on-the-job outcomes, including emerging literature on gender and networks. While there is consensus on the prevalence of social networks in job search there is as yet no consensus on the mechanisms for why referrals are so important: an open question is to uncover systematically the conditions under which different mechanisms are relevant. Second, the literature has documented network effects on labour productivity - mostly when there are no externalities between workers. The findings are that the effects of social ties depend very much on the type of production function assumed. An emerging literature examines whether women benefit from referrals as much as men: gender homophily might play a part in some contexts while in others women confront a bias in referrals. Finally, the literature has moved from use of observational data into lab and field experiments to confront better the challenges of identification.
Keywords: J16; J41; J31; D82; D83; O12; O15; 330; screening; search; labor market; social networks; matching; productivity